Energy Efficient 5G Mobile Communication System Using Transmit Power Control and Small Cell Technique - Meeta Bakuli (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In the realm of next-generation wireless technology, the surge in data traffic poses formidable challenges for communication networks. Addressing these challenges, requires a focus on energy efficiency, particularly in the context of 5G networks where network resources are finite. This paper delves into maximizing energy efficiency by synergizing Demand Power control with the deployment of multiple small cells. Our investigation aims to optimize energy efficiency while ensuring robust data throughput without compromising Quality of Service (QoS). We explore the dynamics of data transmission between the base stations of multiple small cells and their respective users. Data transmission occurs only in response to demand or user requests to the small cell's base station. The strategic deployment of small cells allows users to connect to the nearest cell, enhancing the Signal-to-Noise ratio and consequently improving energy efficiency while reducing energy consumption. Optimal power control ensures that the required data rate and QoS are maintained, leading to maximal Energy Efficiency (EE). The utilization of multiple small cells results in notable enhancements across various metrics. Energy Efficiency (EE), data throughput, and QoS all witness significant improvements compared to a single macrocell at the transmitter base station.